Assesment of the Mechanical Variability of Rock Slabs by Means of Non-Destructive Tests: Analysis Methods (2018)
In this paper is used more and complementary methods of analysis to estimate the mechanical variability of rock slabs by means of non-destructive tests; originally presented in this same journal. The aim is to generalize and improve the applicability of this alternative method, based on geostatistics, for quality control processes of rock slabs destined for floor revetment. Different geostatiscal topics have been emphasized such as data exploratory analysis, anisotropic analysis, verification of the geostatistical model, verification of the spatial structure, verification of the sample size and modeling of the spatial distribution of the mechanical strength.